The Correlation between Family Support and Anxiety of Preoperative Thyroidectomy Patienst in the Surgical Clinic of Mangusada Regional Hospital Badung Regency - Ni Kadek Yani Arianti (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2021)
Background: Disorders of the shape and function of the thyroid cause clinical symptoms and physiological disorders, namely cognitive function, behavioral problems, changes in feelings (mood) and anxiety. Thyroid sufferer's anxiety will increase before thyroidectomy surgery. Family support in preoperative thyroidectomy will be more effective if it comes from a close person who has meaning in an individual's life, who is able to solve problems and reduce anxiety from problems. Objective: This study aims to determine the relationship between family support and anxiety levels of preoperative thyroidectomy patients in the surgical clinic of RSD Mangusada, Badung Regency. Method: The study was conducted with an analytic observational design with a cross sectional approach. The number of samples was 58 respondents using an accidental sampling technique. Data were collected using a family support questionnaire and an anxiety questionnaire. Data were analyzed using the Spearman`s rho test. Method: The result of the study was that most family support was enough as many as 32 people with a percentage of 55.2%. and the most mild anxiety as many as 40 people with a percentage of 69%. Analysis of the relationship between family support and anxiety levels obtained p value <0.001. Conclusion: There is a relationship between family support and the anxiety level of preoperative thyroidectomy patients at the RSD Mangusada Surgery clinic, Badung Regency. The recommendations of this study are expected to be input for nurses to always provide counseling to families by providing motivation to patients who will perform surgery.